Katanin spiral and ring structures shed light on power stroke for microtubule severing - Zehr, Elena; Szyk, Agnieszka; Piszczek, Grzegorz; Szczesna, Ewa; Zuo, Xiaobing; Roll-Mecak, Antonina (Nature structural & molecular biology, 2017)
Using a combination of crystallography, SAXS and cryo-EM, the katanin hexamer is observed in spiral or ring arrangements, suggesting a mechanism to generate the power stroke to severe microtubules. Microtubule-severing enzymes katanin, spastin and fidgetin are AAA ATPases important for the biogenesis and maintenance of complex microtubule arrays in axons, spindles and cilia. Because of a lack of known 3D structures for these enzymes, their mechanism of action has remained poorly understood. Here we report the X-ray crystal structure of the monomeric AAA katanin module from Caenorhabditis elegans and cryo-EM reconstructions of the hexamer in two conformations. The structures reveal an unexpected asymmetric arrangement of the AAA domains mediated by structural elements unique to microtubule-severing enzymes and critical for their function. The reconstructions show that katanin cycles between open spiral and closed ring conformations, depending on the ATP occupancy of a gating protomer that tenses or relaxes interprotomer interfaces. Cycling of the hexamer between these conformations would provide the power stroke for microtubule severing.